HADIS-HADIS KOMUNIKASI PEMBANGUNAN - Irma Yusriani Simamora (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2016)
As one source of religious teachings, traditions, meaning sayings, deeds and approvals as well as the nature of the Prophet, many loading and talk about communication in general and development communication in particular. It certainly is something that is easy and can be understood as Islamic teachings brought by Rasululah certainly conveyed to mankind through communication. On many occasions the Prophet to convey the message that aims to change the belief, attitudes, opinions and behavior in order to make man better, advanced and able to achieve inner satisfaction. For example, the Prophet once declared that the mosque serves as a medium of communication development in Muslim society, worked and continue to work is the key to the progress of individuals and nations, and productivity does not know the time.